Latihan Menelan terhadap Kemampuan Menelan Pasien Stroke yang Mengalami Disfagia - Meszadena Tumanggor; Nunung F. Sitepu; Kiking Ritarwan (Journal of Telenursing (JOTING), 2023)
This study aims to identify and compare the effect of interventional swallowing exercises on swallowing ability in stroke patients who experience dysphagia. The method used is a quantitative method with a one-group pre-test-post-test approach. Respondents in this study were stroke patients who underwent moderate category of dysphagia, totaling 35 respondents. Initial data collection was started using the Nursing Bedside Swallowing Screening dysphagia assessment sheet. Then, the researcher used the Mann Assessment of Swallowing Ability (MASA) to assess the patient's swallowing ability. The results showed a significant difference (p<0.05) in the swallowing capacity of the respondents before and after the swallowing training intervention. The conclusion of this study, swallowing exercises are effective in improving the swallowing ability of stroke patients who experience dysphagia. Keywords: Dysphagia, Swallowing Ability, Stroke